2005
DOI: 10.1111/j.1478-3231.2004.0985.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing frequency of Gram‐positive bacteria in spontaneous bacterial peritonitis

Abstract: Culture-positive SBP in cirrhotic patients are caused more frequently by Gram-positive bacteria during the recent years, which are, in their vast majority, resistant to quinolones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 14 publications
8
71
2
2
Order By: Relevance
“…They found a higher proportion of quinolone-resistant gram-negative bacilli infections among patients receiving norfloxacin prophylaxis but found no difference by duration of norfloxacin therapy. Cholongitas et al 32 reported that gram-positive bacteria caused SBP in their patients significantly more frequently during 2000-2002 than during 1998-1999 (P ϭ 0.04). Interestingly, none of their patients had been receiving prophylactic antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…They found a higher proportion of quinolone-resistant gram-negative bacilli infections among patients receiving norfloxacin prophylaxis but found no difference by duration of norfloxacin therapy. Cholongitas et al 32 reported that gram-positive bacteria caused SBP in their patients significantly more frequently during 2000-2002 than during 1998-1999 (P ϭ 0.04). Interestingly, none of their patients had been receiving prophylactic antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The applicability in the clinical practice of a guideline derived from randomized controlled investigations is very important. Moreover, such analysis is also justified by the evidence that the type and etiology of bacterial infections in cirrhosis may have changed during recent years [14][15][16][17][18] . For this purpose, the results of patients' management according to these guidelines were evaluated in an unselected group of cirrhotic patients with SBP consecutively observed in the last three-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there have been suggestions that the type and etiology of bacterial infections in cirrhosis may have changed during recent years [14,15] . An increasing incidence of SBP caused by Gram-positive bacteria in cirrhotic patients with ascites has been observed by different authors [16,17] . In addition, an increased frequency of bacteria resistant to multiple antibiotics has been shown [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Our findings clearly demonstrated that intestinal decontamination with rifaximin resulted in a significant reduction in the mean serum levels of the pro-inflammatory cytokines (TNF-α and IL-6) and a significant increase in the serum level of the anti-inflammatory cytokine (IL-10). Recurrence of SBP episodes in patients on norfloxacin therapy was due to gram-positive organisms that are not sensitive to this therapy (26). Both rifaximin and norfloxacin showed a statistically significant decrease in serum TNF-α and IL-6 levels in comparison with their baseline data.…”
Section: Mostafa Et Al the Efficacy Of Rifaximin The In Prophylaxis mentioning
confidence: 81%
“…Furthermore, rifaximin has better activity against gram-positive organisms over norfloxacin (10). This is very important, particularly with increasing frequency of gram-positive bacteria in spontaneous bacterial peritonitis (26).…”
Section: Mostafa Et Al the Efficacy Of Rifaximin The In Prophylaxis mentioning
confidence: 99%